Cymbidium purpureisepalum (Orchidaceae; Epidendroideae), a new species from China: evidence from morphological and molecular data - Zhu, Meng-Jia; Ke, Shijie; Zhao, Xuewei; Wang, Qian-Qian; Chen, Guizhen; Liu, Zhong-Jian; Lan, Siren (Phytotaxa, 2022)
A new orchid species, Cymbidium purpureisepalum, from Yunnan Province, China, is described and illustrated based on morphological and molecular analyses. Detailed comparison of the newly discovered orchid with other members of Cymbidium indicated the new orchid is distinct from all other recognised species in Cymbidium. Molecular analyses based on nuclear (nrITS) and plastid DNA (matK) sequence data also support the status of C. purpureisepalum as a new species, which is sister to C. tortisepalum and C. serratum.